Attentional Bias Modification for Social Anxiety Disorder: What do Patients Think and Why does it Matter?. Issue 1 (6th May 2018) - Kuckertz, Jennie M.; Schofield, Casey A.; Clerkin, Elise M.; Primack, Jennifer; Boettcher, Hannah; Weisberg, Risa B.; Amir, Nader; Beard, Courtney
Abstract : Background: In the past decade, a great deal of research has examined the efficacy and mechanisms of attentional bias modification (ABM), a computerized cognitive training intervention for anxiety and other disorders. However, little research has examined how anxious patients perceive ABM, and it is unclear to what extent perceptions of ABM influence outcome.Aims: To examine patient perceptions of ABM across two studies, using a mixed methods approach.Method: In the first study, participants completed a traditional ABM program and received a hand-out with minimal information about the purpose of the task. In the second study, participants completed an adaptive ABM program and were provided with more extensive rationale and instructions for changing attentional biases.Results: A number of themes emerged from qualitative data related to perceived symptom changes and mechanisms of action, acceptability, early perceptions of the program, barriers/facilitators to engagement, and responses to adaptive features. Moreover, quantitative data suggested that patients' perceptions of the program predicted symptom reduction as well as change in attentional bias.Conclusions: Our quantitative data suggest that it may be possible to quickly and inexpensively identify some patients who may benefit from current ABM programs, although our qualitative data suggest that ABM needs major modifications before it will be an acceptable and credible treatment more broadly. Although the current study was limited by sample size and design features of the parent trials from which these data originated, our findings may be useful for guiding hypotheses in future studies examining patient perceptions towards ABM.